Scenic Skins - Teaching characterization makeup in a methodological transformation in artistic-pedagogical training (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This article is a research project conducted in the Graduate Program in Performing Arts Education – Professional Master's Program at the Federal University of the State of Rio de Janeiro (UNIRIO). The research is based on an analytical and photographic memorial about my own research process as an artist-researcher-teacher and the methodological development with students at the institutions and art spaces where we worked on the teaching and learning of makeup, from 2016 to 2023. The research organizes the recognition of the creation of a methodology for makeup, based on photographs, texts, and student testimonies. It analyzes this movement in a public institution in Minas Gerais and seeks to reveal its different methodological possibilities, how this transformation occurred in the teaching and learning process, and its consequences for the teaching of Costume Design in another public institution.
Keywords: makeup; characterization; teaching-learning; scene